Hindī rāshṭrīya Mahāsabhānuṃ bandhāraṇa : tā. 24-25 Aiprila 1948, ne roja Mumbaīnī Mahāsamitinī beṭhakamāṃ mañjūra thayeluṃ (SAMP early 20th-century Indian books project ;, 1948)
On Indian National Congress.